2021
DOI: 10.15237/gida.gd21011
|View full text |Cite
|
Sign up to set email alerts
|

YARPUZ (Mentha pulegium L.) TOZU İLE FORMÜLE EDİLEN SIĞIR KÖFTELERİNİN FİZİKOKİMYASAL VE DUYUSAL KALİTESİNİN DEĞERLENDİRİLMESİ

Abstract: The present study was conducted to evaluate the physicochemical and sensory quality of beef patties containing different levels of pennyroyal powder (PP) during storage at 4 °C for up to 9 days. The PP was added to patties at 0.75, 1.5, 2.25, and 3.0% levels and compared to negative (without PP) and positive controls (0.01% propyl gallate). The PP addition decreased the protein content and increased the ash content (P <0.05). The PP inclusion improved cooking loss, but negatively affect the hardness and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Carnosic acid that was extracted from rosemary leaves was found to show significant antioxidant activity in cooked ground buffalo meat at low concentrations (22.5 ppm) (Zang et al, 2022). Pennyroyal (Mentha pulegium L.) powder when added to beef patties significantly reduced in lipid oxidation (Guliyeva and Turhan, 2021). Extracts from rosemary (rosmaridiphenol, rosmariquinone), green tea (epigallocatechins, catechins), and red pepper (capsaicinoids) were tested for their efficacy to control oxidation in pork meat products and it was found that these extracts effectively controlled the lipid oxidation (Yoon et al, 2021).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Similarly, Carnosic acid that was extracted from rosemary leaves was found to show significant antioxidant activity in cooked ground buffalo meat at low concentrations (22.5 ppm) (Zang et al, 2022). Pennyroyal (Mentha pulegium L.) powder when added to beef patties significantly reduced in lipid oxidation (Guliyeva and Turhan, 2021). Extracts from rosemary (rosmaridiphenol, rosmariquinone), green tea (epigallocatechins, catechins), and red pepper (capsaicinoids) were tested for their efficacy to control oxidation in pork meat products and it was found that these extracts effectively controlled the lipid oxidation (Yoon et al, 2021).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…The extraction of phenolic compounds was carried out according to the procedure explained by Guliyeva and Turhan (2021). Firstly, 5 g of PS was mixed with 20 mL of 80% methanol aqueous solution and submitted to ultrasound for 15 min.…”
Section: Extraction Proceduresmentioning
confidence: 99%